Gender Differences in Obesogenic Behaviour, Socioeconomic and Metabolic Factors in a Population-based Sample of Iranians: The IHHP Study (Journal of Health, Population and Nutrition, 2010)
This study investigated the gender differences in association of some behavioural and socioeconomic factors with obesity indices in a population-based sample of 12,514 Iranian adults. The mean body mass index (BMI), waist circumference (WC), and the waist-to-hip ratio (WHR) were significantly higher in women than in men. Current and passive smoking had an inverse association with BMI among males whereas current smoking, transportation by a private car, and longer duration of watching television (TV) had a positive association with BMI among females. Current and passive smoking, cycling, and Global Dietary Index (GDI) had an inverse association with WC among males. Higher consumption of fruits and vegetables, current and passive smoking, duration of daily sleep, and GDI had an inverse association with WC among females. Using a private car for transportation had a significant positive association with WHR among both males and females. Living in an urban area, being married, and having a higher education level increased the odds ratio of obesity among both the genders. Non-manual work also increased this risk among males whereas watching TV and current smoking increased this risk among females. Such gender differences should be considered for culturally-appropriate interventional strategies to be implemented at the population level for tackling obesity and associated cardiometabolic risk factors. Key words: Cardiovascular diseases; Cross-sectional studies; Lifestyle; Obesity; Risk factors; Socioeconomic factors; IranDOI: 10.3329/jhpn.v28i6.6609J HEALTH POPUL NUTR 2010 Dec;28(6):602-609